(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article is devoted to the main trends in the evolution of religious symbols. The stages of emergence, formation and development of religious symbols, as well as factors contributing to their timely change are presented in this article. It is known that the appearance of religious symbols and their further evolution are directly related to the development of religious consciousness. According to the study, religious consciousness exists on two levels and corresponds to the stages of development of religion. First, religious consciousness originated in the primitive era at the level of social psychology, as a spontaneous expression in the form of religious images, ideas, feelings, traditions, etc. practical impotence of people before the domination of natural and social forces, then the system of religious ideologies, that is, religious ideas and ideas based on social psychology during the formation of a system of social relations. Religious symbols changed according to the peculiarities of historical eras, and depending on the requirements of the religious beliefs of society. Thus, by studying the evolution of religious symbols and tendencies in it, conclusions can be drawn: religious symbols changed in accordance with the needsof the public consciousness in historical eras, and interested representatives of religious denominations contributed to this. Key words: religion, religious consciousness, myth, mythology, pre-symbol, pre-symbol, religious symbol, symbolization, evolution, transformation.